Information security investment prioritization using best-worst method for small and medium enterprises - Alva Hendi Muhammad; Joko Dwi Santoso; Ananda Fikri Akbar (Institute of Advanced Engineering and Science, 2023)
In recent years, cyber security has become an increasingly important aspect of the decision-making process of corporations. It is essential to make investments in cybersecurity at this point to guard against the frequent disruption of business operations posed by cyberattacks. In the context of small and medium-sized organizations, this study recommends using a multicriteria decision-making technique to evaluate information security aspects. The information security index is derived as the foundation for every one of these features. The best-worst method is carried out to establish the best and worst possible security investments. In order to validate these findings, a survey was distributed to a variety of professionals and business decisionmakers. The criteria for selection are laid forth in the form of categories labeled technology and organization, respectively. The findings are presented in a rating system with three tiers, with the highest level representing the absolute best of the results. In the final section of the study, we will examine potential future possibilities for research and policy.